Effect of Bi doping on the structure and wave absorption properties of barium ferrite. Issue 3 (1st February 2022) - Chen, Yucheng; Cheng, Lichun; Xia, Tianrui; Wang, Man; Zhou, Huaiying; Yao, Qingrong; Zhai, Yuhang
Abstract: Bi x Ba1- x Fe12 O19 (Bi–BFO, x = 0, 0.1, 0.2, 0.3, 0.4) absorbing materials were successfully prepared employing the sol-gel method. In this study, the effects of Bi introduction on the phase structure, microstructure, magnetic properties, and wave absorption properties of the materials were investigated in detail. The introduction of Bi enhances the dielectric properties and electrical conductivity of the material, which improves charge and dipole polarization. Elemental doping changes the microstructure of the sample, which leads to interface and defect polarization and improves the wave absorption performance of the material. At the same time, Bi doping allows for the calcination temperature to be lowered and increases the density of the material, which renders the material amenable to low-temperature preparation. The absorbing material has a variety of loss forms, with the maximum reflection loss being −43.6 dB when the thickness is 2.4 mm, and the reflection peak shifts to lower frequencies with increasing Bi content. The effective absorption bandwidth (RL < −10 dB) is 6.3 GHz in the range of 9–15.3 GHz. Compared with multi-element doping and multi-component composites, the preparation method of the absorbing material is simple and facile. Compared with the existing ferrite materials, this material has broader applicability in various fields as it can absorb a wider bandwidth.